Konsistensi Hukum Hadhanah Di Indonesia: Studi Yuridis Normatif Terhadap Putusan Pengadilan - Hasna Putri, Nabila; Tahir, Palmawati; Muslih, Muhamad (Qanun: Jurnal Hukum Keluarga Islam, 2023)
Hadhanah is one of the important aspects regulated in Indonesian law. This can be seen from the existence of Hadhanah which is regulated in Article 105 letter (a) of the 1991 Presidential Instruction of the Republic of Indonesia concerning the Compilation of Islamic Law which regulates that after a divorce, the care of a child who is not mumayyiz or not yet twelve years old is the right of the mother. This is different from the judge's decision number 4391/Pdt.G/2021/PA.JS which stipulates that custody of children who are not yet mumayyiz is given to the father as the defendant. Based on these problems, the researcher formulated an identification problem, namely what was the basis for the judge's considerations and how the legal consequences of the court decision were connected to the Marriage Law and the Compilation of Islamic Law. Then the researcher used the theory of justice and the theory of legal certainty. Then the research method used is normative juridical, with research specifications in the form of a statutory approach and a case approach. The conclusion of this research is that the judge gave custody of the child who had not yet mumayyiz into the hands of the father based on several considerations by not only prioritizing legal formalities, but also considering the best interests of the child.